Analysis of different annealing conditions on physical properties of Bi doped CdTe thin films for potential absorber layer in solar cells. (15th March 2020) - Himanshu; Patel, S.L.; Thakur, A.; Kannan, M.D.; Dhaka, M.S.
Highlights: Analysis of different annealing conditions on CdTe:Bi films is reported. Structural properties reveal to cubic phase with preferred (1 1 1) plane. Optical band gap is found 1.42 eV for 300 °C air annealed films. Surface morphology reveals to homogenous deposition of films. Air annealed films at 300 °C are found more suitable for potential absorber. Abstract: The mainstream technology used for production of high-efficiency CdTe photovoltaics involves Cu doping to CdTe absorber and CdTe/CdS junction activation by cadmium chloride (CdCl2 ), however, both procedures restrict their use for long term operation. With purpose of seek alternatives, herein, air and MgCl2 annealing along with CdCl2 is performed over e-beam evaporated CdTe:Bi films for their role in absorber photovoltaics. Structural properties indicate appearance of cubic (1 1 1) preferred peak where grain size is found to be affected with nature and temperature of annealing. Optical properties divulge variation in absorbance with annealing, also direct energy band gap is estimated in 1.42–1.69 eV range. All investigated films demonstrated ohmic behavior where conductivity is affected by Bi dopant. Surface morphological properties demonstrated uniform deposition with spherical-shaped grains for pristine as well as 150 °C and 300 °C air annealed films which changed to polyhedral at further annealing. Appeared Cd and Te peaks in EDS patterns validated CdTe films deposition. Surface topographical properties display ditch and dike structures for pristine and 150 °C annealing and hillock structures for higher annealing. Thus, present study imparts critical insights to air, CdCl2 and MgCl2 annealing effect on properties to CdTe:Bi films and designate that chloride treatment is less-effective during Bi doping to CdTe.